Comparison of the degree of mangrove species association among selected sites in the province of Iloilo, Panay Island, Philippines. - Coching, Jofel Delfin
Mangrove species composition of one area varies from another. This research paper was conducted to determine the degree of mangrove species association among sampling sites in Iloilo namely Ajuy, Balasan Barotac Viejo, Zarraga, Barotac Nuevo, and Tigbauan. It also aimed to compute for the Importance Value (IV) for each mangrove species and compute for the Jaccard's Coefficient (CCj) for the sampling sites. These values indicate the most important species in each area and as well as the similarity between sites. The findings of this study can serve as basis for restoration and reforestation projects of concerned institutions. A total of 28 species belonging to 14 families were present in all areas sampled but different in each municipality. Ajuy had 26 species in 14 families; Balasan had 19 species of true mangroves belonging to 12 families; Estancia had 20 species belonging to 10 families; Barotac Viejo had 18 species belonging to 11 families; Barotac Nuevo had 19 species in 11 families Tigbauan had 9 species belonging to 6 famlies; Zarraga had 21 species in 10 families. From all the sampling sites, there are a total of 28 species belonging to 14 families. The sites with the greatest similarity in species composition are Estancia and Barotac Viejo with Jaccard's Coefficient (CCj) of 0.810, thus being mostly associated. The sites with the least similarity in species composition are Tigbauan and Barotac Viejo (CCj) of 0.36. The most dominant species in Balasan and Estancia is Sonneratia alba, Nypa fruiticans dominated both Barotac Viejo and Tigbauan; Avicennia marina dominated Ajuy; Avicennia marina and Sonneratia alba dominated Zarraga. The Importance Value (IV) of Sonneratia alba was highest to both Balasan (1.07) and Estancia (1.3376); Avicennia marina (1.7417) was the most important species in Barotac Viejo, Ajuy (1.787) and Zarraga (1.6743); Nypa fruiticans (1.486) had the highest IV in Tigbauan. Species distribution and importance value of mangroves in these areas could be influenced by both intraspecific (i.e. temperature, light, salinity, pH, tides and ocean currents, and substrate type) and interspecific factors (i.e., size, weight, dispersal ability, and longetivity of seeds).